2019
DOI: 10.3390/rs11182138
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interannual Urbanization of China’s Six Megacities Since 2000

Abstract: As a large and populous developing country, China has entered the rapid urbanization stage since 2000. Until 2018, China has accounted for nearly 1/5 of global megacities. Understanding their urbanization processes is of great significance. Given the deficiencies of existing research, this study explored the interannual urbanization process of China's six megacities during 2000-2018 from four aspects, namely, the basic characteristics of urban land expansion, expansion types, cotemporary evolution of urban lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…For instance, AGRs of megacities in Asia and Africa were greater than those in Europe, which was consistent with Taubenböck's conclusions (Taubenböck et al 2012). Besides, several existing studies proposed that urban expansion and population increase could be affected by natural terrain and transportation (Yu, Zhang, and Liu 2019;Yu et al 2019a). As its strong standpoint, this study found that inland megacities showed a 'mononuclear and concentric circle' expansion mode, whereas the coastal ones expanded according to a 'bidirectional and narrow shape' mode ( Figure 3).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, AGRs of megacities in Asia and Africa were greater than those in Europe, which was consistent with Taubenböck's conclusions (Taubenböck et al 2012). Besides, several existing studies proposed that urban expansion and population increase could be affected by natural terrain and transportation (Yu, Zhang, and Liu 2019;Yu et al 2019a). As its strong standpoint, this study found that inland megacities showed a 'mononuclear and concentric circle' expansion mode, whereas the coastal ones expanded according to a 'bidirectional and narrow shape' mode ( Figure 3).…”
Section: Discussionsupporting
confidence: 79%
“…During the past several decades, the economic and cultural exchanges in this region have created special conditions for the formation and expansion of local cities. Surpassing other types of cities in both inhabitants and physical size, the megacity is regarded as an important city form that reflects national urbanization characteristics (Liu et al 2016;Yu et al 2019a). Concentrating nearly 60% of global megacities, the B&R is undoubtedly an appropriate region for researching the urbanization processes of megacities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the previous studies that usually use edge-expansion, infilling, and leapfrogging to define urban extension types, this paper provided a new method that combined absolute and relative speed to define urban extension types. When grading the single index after standardization, both Shi et al and Yu et al used −1, 0, and 1 as breakpoints for grading [40,46]. However, different data sets can have different distribution characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In all six cities, the growth of GDP greatly exceeded the growth of urban land area. Yu et al [46] found that there was an obvious log-linear relationship between urban land and population, as well as between urban land and GDP. Moreover, the slope of the former was higher than that of the latter, indicating that, although both population and GDP had a positive impact on urban land, the increase in population had a more significant impact on urban land than GDP.…”
Section: Literature Reviewmentioning
confidence: 99%